Evaluation of the actual reality of supply chain operations in Noor Al-Kafeel Food Products Company/ case study. (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:                This research aims to identify the actual reality of the supply chain processes applied in the Noor Al-Kafeel Food Products Company, which was chosen as a research sample by measuring the application and documentation gap. The current research relies on the case study method to reach the desired results, and the seven-scale scale was relied on to identify the reality of the supply chain operations applied in the researched company and the use of quantitative and qualitative methods in data collection and analysis, as quantitative methods such as the arithmetic mean were used weighted, percentage measurement, and gap size measurement, while qualitative methods included field visits, personal observation, direct interviews, and access to records and documents. Data was collected using a checklist that included seven axes (purchasing, storage, production, distribution, transportation, customer service and information), which fall under the concept of supply chain operations in order to diagnose the actual reality of those operations in the company and determine which operations are the most important. interest and least interest in the company. The most important results of this study were represented in the fact that there is a gap between the indicators of the supply chain and the reality of the work of the researched company at a rate of (28.23%) distributed among the axes of these operations.